2011
DOI: 10.1038/ng.994
|View full text |Cite
|
Sign up to set email alerts
|

Ollier disease and Maffucci syndrome are caused by somatic mosaic mutations of IDH1 and IDH2

Abstract: Ollier disease and Maffucci syndrome are characterized by multiple central cartilaginous tumors that are accompanied by soft tissue hemangiomas in Maffucci syndrome. We show that in 37 of 40 individuals with these syndromes, at least one tumor has a mutation in isocitrate dehydrogenase 1 (IDH1) or in IDH2, 65% of which result in a R132C substitution in the protein. In 18 of 19 individuals with more than one tumor analyzed, all tumors from a given individual shared the same IDH1 mutation affecting Arg132. In 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
300
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(320 citation statements)
references
References 10 publications
11
300
0
9
Order By: Relevance
“…Previous studies found IDH mutations in a variety of benign and malignant musculoskeletal tumors, including osteosarcomas and giant cell tumors of bone (16,31,32). Furthermore, the mouse mesenchymal cell line C3H10T1/2 expressing the IDH2 R172K mutation can give rise to poorly differentiated sarcomas in xenograft models (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found IDH mutations in a variety of benign and malignant musculoskeletal tumors, including osteosarcomas and giant cell tumors of bone (16,31,32). Furthermore, the mouse mesenchymal cell line C3H10T1/2 expressing the IDH2 R172K mutation can give rise to poorly differentiated sarcomas in xenograft models (17).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of enchondromas and chondrosarcomas harbor somatic isocitrate dehydrogenase 1 (IDH1) or IDH2 mutations (15)(16)(17)(18). Mutations in IDH genes are common in several other neoplasms, including glioma, glioblastoma, acute myeloid leukemia, angioimmunoblatic T-cell lymphoma, and intrahepatic cholangiocarcinomas (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Mutations in IDH1 and IDH2 were found in 75% of grade 2 to 3 gliomas and secondary glioblastoma, and in about 20% of AML [36][37][38][39][40][41][42][43][44][45][46][47][48]. Following the discovery in glioma and AML, IDH1 and IDH2 mutations were also found in several other human tumors, including cartilaginous tumors (75%) [49][50][51], intrahepatic cholangiocarcinoma (10%) [52,53], thyroid carcinomas (16%) [54,55], and less frequently in prostate cancer, acute B-lymphoblastic leukemia, paragangliomas, colorectal carcinoma, and melanoma [52,56,57]. Thus, IDH1 and IDH2 represent the most frequently mutated metabolic genes in human cancer ( Table 1).…”
Section: Idh1 and Idh2 Are Most Frequently Mutated Metabolic Genes Inmentioning
confidence: 99%
“…Moreover, elevated 2-HG levels in the brain result in increased reactive oxygen species (ROS) concentrations, potentially contributing to an increased risk of cancer (Kolker et al 2002). IDH1/2 mutations occur in some gliomas ), cartilaginous tumors (Amary et al 2011;Pansuriya et al 2011), and in acute myeloid leukemias (Ward et al 2010). In astrocytomas, oligodendrogliomas, oligoastrocytomas, and secondary glioblastomas, IDH1/2 mutations have been identified as early and frequent genetic alterations (50-93%).…”
Section: Introductionmentioning
confidence: 99%